M. tuberculosis infection and antigen specific cytokine response in healthcare workers frequently exposed to tuberculosis - Essone, Paulin N. (Sci Rep, 2019)
Tuberculosis (TB) is the leading cause of death due to an infectious agent, but only a small fraction of those infected develop the disease. Cytokines are involved in the mediation and regulation of immunity, and their secretion patterns may reflect the infection status. To increase our understanding of immune response to M. tuberculosis infection, we conducted a cross-sectional study investigating M. tuberculosis infection status and comparing the release profiles of cytokines GM-CSF, IFN-γ, IL-1β, IL-10, IL-12 (p70), IL-2, IL-4, IL-5, IL-6, IL-8, TNF-α, in community controls (CCs) and healthy healthcare workers (HCWs) highly exposed to TB. Among HCWs and CCs, the probability of latent M. tuberculosis (LTB(+)) infection was respectively 5.4 (p = 0.002) and 3.4 (p = 0.006) times higher in men than women. The odds ratio of LTB infection was 4 times higher among HCWs in direct contact with active TB patients than other HCW (p = 0.01). Whole blood supernatant cytokine responses to M. tuberculosis antigens showed differential pro-inflammatory responses between HCWs and CCs. CCs(LTB−) had higher IL-1β responses than HCWs(LTB−) (p = 0.002). HCWs(LTB+) had significantly higher IL-8 responses to M. tuberculosis antigens than HCWs(LTB−) (p = 0.003) and CCs(LTB−) (p = 0.015). HCWs(LTB+/−) showed weak but positive TNF-α responses to M. tuberculosis antigen stimulation compared to CCs(LTB+/−) (p ≤ 0.015). Looking at T-helper (1 and 2) responses, HCWs(LTB+) and CCs(LTB+) had significantly higher IFN-γ and IL-2 responses compared to HCWs(LTB−) and CCs(LTB−) (p < [0.0001–0.003]). Also, TB antigen induced IL-5 secretion was significantly higher in HCWs(LTB+) and CCs(LTB+) than in non-infected CCs(LTB−) (p < [0.005–0.04]). M. tuberculosis antigen specific responses in HCWs(LTB+) varied based on active TB exposure gradient. HCWs(LTB+) who were highly exposed to active TB (≥3 hours per day) had significantly higher IFN-γ and IL-8 responses (p ≤ 0.02) than HCWs (LTB+) not in direct contact with active TB patients. HCWs(LTB+) working with active TB patients for 5 to 31 years had a significantly enhanced secretion of proinflammatory cytokines (GM-CSF, IFN-γ, IL-1β, IL-2, IL-6, IL-8, IL-12p70, TNF-α) compared to HCWs(LTB−) (p < [0.0001–0.01]). Secretion of anti-inflammatory/Th2 cytokines IL-5 and IL-10 was also higher in HCWs(LTB+) than HCWs(LTB−). In conclusion, LTBI individuals controlling the M. tuberculosis infection have an enhanced TB specific Th1-cytokines/proinflammatory response combined with selected Th2 type/anti-inflammatory cytokines induction.